2018
DOI: 10.1111/jre.12527
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein modifications by gingipains of Porphyromonas gingivalis

Abstract: Background and ObjectiveSeveral studies have shown an association between periodontitis and cardiovascular disease (CVD). Atherosclerosis is the major cause of CVD, and a key event in the development of atherosclerosis is accumulation of lipoproteins within the arterial wall. Bacteria are the primary etiologic agents in periodontitis and Porphyromonas gingivalis is the major pathogen in the disease. Several studies support a role of modified low‐density lipoprotein (LDL) in atherogenesis; however, the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 49 publications
1
32
0
2
Order By: Relevance
“…Arginine residue dissolution from l-arginine occurs after hydrolysis participates in the formation of the arginine-specific cysteine proteinase (Arg-gingipain) of P. gingivalis [23]. Gingipain can activate the production of reactive oxygen species and induce peroxidation to induce the inflammation and destruction of periodontal tissues [24]. Thus, the aim of the present study was to establish the P. gingivalis biofilm and investigate the effects of d-arginine in inhibiting and disassembling the P. gingivalis biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Arginine residue dissolution from l-arginine occurs after hydrolysis participates in the formation of the arginine-specific cysteine proteinase (Arg-gingipain) of P. gingivalis [23]. Gingipain can activate the production of reactive oxygen species and induce peroxidation to induce the inflammation and destruction of periodontal tissues [24]. Thus, the aim of the present study was to establish the P. gingivalis biofilm and investigate the effects of d-arginine in inhibiting and disassembling the P. gingivalis biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…LDL modification in vascular compartment may occur as a result of proteolytic effects of P. gingivalis and/or leukocyte proteases or by the oxidative burst response of phagocytes in the blood to P. gingivalis . LDL was reported to form aggregates with P. gingivalis and its outer membrane vesicles (OMV).…”
Section: Discussionmentioning
confidence: 99%
“…161 The activity of P. gingivalis and its virulence factors may also contribute to the increased cardiovascular disease risk in RA and Parkinson's disease (PD) patients. 162,163 It has been demonstrated that Arginine-specific gingipains (RgpA, RgpB) are able to activate the coagulation cascade at multiple levels. Gingipains proteolytically stimulate coagulation factors IX, 164 X, 165 and II (prothrombin).…”
Section: Involvement Of Bacterial Components In Immunopathogenesis Anmentioning
confidence: 99%
“…167 The proteolytic activities of the virulence factors of P. gingivalis have been shown to degrade apolipoproteins essential for normal lipoprotein metabolism, producing proinflammatory and proarthritogenic events that could account for increased risk of atherosclerosis. 162 The proteolysis of human fibrinogen through the combined effect of PPAD and RgpB inhibits fibrin polymerization, which results in localized bleeding and a potentially dysregulated coagulation cascade. 168 Rgp is able to activate platelets via platelet activation receptors one (PAR-1) and four (PAR-4).…”
Section: Involvement Of Bacterial Components In Immunopathogenesis Anmentioning
confidence: 99%